Generation and Development of Psychological and Pedagogical Ideas of O.F.Lazurskyi According to his Correspondence - Inna Leontyevа (Pedagogical Discourse, 2013)
An important part of the creative heritage of the scientist is his epistolary. It is of scientific interest not only as a way of getting closer to the science lab and the study of his biography, but also as the original factor, which displays the multifacetedness of there searcher’s spiritual life, individual features of his thinking, principles of work and creative plans. In the article the letters of an outstanding scientist, psychologist and teacher A.F.Lazurskogo, which expose his life and creative career, scientific and world outlook on the background the major events of public life of the Russian empire of the end of ХІХ and the beginning of ХХ  century are analysed.